Transcatheter arterial perfusion chemotherapy combined with lipiodol chemoembolization for advanced colorectal cancer complicated by obstruction - Ding, Xiaolong; Ma, Yaozhen; Yin, Meipan; Liu, Tao; Jin, Shuiling; Li, Chunxia; Li, Xiaobing; Zhang, Chenchen; Zhou, Gang; Wu, Gang (Frontiers in Oncology, 2024)
Background: Obstruction is a common complication of advanced colorectal cancer.This study was aimed at investigating the safety, efficacy, and feasibility of transcatheter arterial perfusion chemotherapy combined with lipiodol chemoembolization for treating advanced colorectal cancer complicated by obstruction.Patients and Methods: This retrospective analysis was conducted using clinical data of patients with advanced colorectal cancer who received arterial infusion chemotherapy combined with lipiodol chemoembolization treatment at our center.Treatment efficacy was evaluated in terms of obstruction-free survival and overall survival, and treatment complications were monitored.Results: Fifty-four patients with colorectal cancer complicated by obstruction were included. All patients successfully underwent transcatheter arterial infusion combined with lipiodol chemoembolization treatment. The average lipiodol dose administered was 2.62 ± 1.45 ml (0.5-5.5 ml). No serious complications such as perforation or tumor dissemination occurred. The clinical success rate was 83.3% (45/54). One month after treatment, the objective response rate (ORR) and disease control rate (DCR) were 66.67% and 88.9%, respectively. The median obstruction-free survival was 5.0 months. No serious adverse events occurred. As of the last follow-up, 6 patients survived, 44 died, and 4 were lost to follow-up.Our findings revealed that transcatheter arterial infusion chemotherapy combined with lipiodol chemoembolization is safe and effective for treating advanced colorectal cancer complicated by obstruction. It may serve as a new treatment strategy for patients with advanced colorectal cancer complicated by obstruction.